Peningkatan kecerdasan spiritual Islam perspektif Syaikh al-Islam Ibnu Taimiyah dalam Kitab Al-Tuhfah al-‘Iroqiyyah - Supraha, Wido; Rahman, Taufik Nur; Ahmad, Ahmad (TAWAZUN: Jurnal Pendidikan Islam, 2022)
Islamic education always upholds spiritual values such as faith and piety to Allah in every educational process and instills these spiritual values into the hearts of students so that they believe that spiritual values are the main basis in carrying out their lives. Spiritual intelligence is closely related to intellectual intelligence and emotional intelligence even intellectual and emotional intelligence cannot be balanced without being accompanied by spiritual intelligence. Knowing the magnitude of the benefits of spiritual intelligence for students in an educational process, it is necessary to have a method in increasing spiritual intelligence to make it easier to achieve the goals of Islamic education itself. This paper aims to find out how to increase the spiritual intelligence of the perspective of Sheikh al-Islam Ibn Taimiyah in the At-Tuhfah al-'Iroqiyyah book. This study uses a qualitative approach with library research type, the primary data source in this study is At-Tuhfah al-'Iroqiyyah by Sheikh al-Islam Ibn Taimiyah while the secondary data in this study is the work of Muslim scholars and scholars who focus on discussing soul cleansing and spiritual intelligence. Based on the analysis of the book At-Tuhfah al-'Iroqiyyah by Shaykh al-Islam Ibn Taimiyah, it can be concluded that increasing spiritual intelligence must be based on cleansing the soul of things that can hinder the increase in spiritual intelligence.AbstrakPendidikan Islam selalu menjunjung tinggi nilai-nilai spiritual seperti keimanan dan ketakwaan kepada Allah ï‰ dalam setiap proses pendidikannya serta menanamkan nilai-nilai spiritual tersebut ke dalam hati peserta didiknya agar mereka yakin bahwa nilai spiritual itulah yang menjadi dasar utama dalam menjalankan kehidupannya. Kecerdasan spiritual sangatlah berkaitan erat dengan kecerdasan intelektual dan kecerdasan emosional bahkan kecerdasan intelektual dan emosional tidak dapat seimbang tanpa diiringi dengan kecerdasan spiritual. Mengetahui besarnya manfaat kecerdasan spiritual bagi peserta didik dalam sebuah proses pendidikan maka perlu adanya sebuah metode dalam meningkatkan kecerdasan spiritualnya guna mempermudah dalam mencapai tujuan pendidikan Islam itu sendiri. Tulisan ini bertujuan untuk mengetahui cara peningkatan kecerdasan spiritual perspektif Syaikh al-Islam Ibnu Taimiyah Dalam Kitab At-Tuhfah al-‘Iroqiyyah. Penelitian ini menggunakan pendekatan kualitatif dengan jenis library research, sumber data primer pada penelitian ini adalah At-Tuhfah al-‘Iroqiyyah karya Syaikh al-Islam Ibnu Taimiyah sedangkan data sekunder pada penelitian ini adalah karya para ulama dan cendekiawan muslim yang fokus membahas tentang pembersihan jiwa dan kecerdasan spiritual. Berdasarkan analisa terhadap kitab At-Tuhfah al-‘Iroqiyyah karya Syaikh al-Islam Ibnu Taimiyah dapat disimpulkan bahwa dalam meningkatkan kecerdasan spiritual harus didasari dengan membersihkan jiwa dari hal-hal yang dapat menghambat peningkatan kecerdasan spiritualnya.